Genetic variability in exotic cowpea (Vigna unguiculata L.) genotypes (Asian Journal of Medical and Biological Research, 2024)
Genetic variability plays a crucial role in hybridization and the development of crops with desirable traits. This study, conducted at the Regional Agricultural Research Station of the Bangladesh Agricultural Research Institute in Chattogram, focused on assessing genetic diversity, correlations, and path coefficients related to yield and other traits in 31 cowpea genotypes. The experiment, designed as a randomized complete block with three replications, revealed significant differences among the genotypes for all traits measured, as confirmed by analysis of variance. While most traits showed minimal differences between phenotypic and genotypic variances, plant height and yield per plant were more significantly influenced by environmental factors. The coefficients of variation were low for days to first flowering, days to 50% flowering, days to maturity, and days to harvesting; moderate for seeds per plant; and high for other traits. Plant height, thousand-seed weight, and yield per plant exhibited high heritability and substantial genetic advance, suggesting that direct selection for these traits would be effective due to their additive genetic control. The correlation analysis indicated significant positive relationships between yield per plant and several flowering and maturity traits at both the genotypic and phenotypic levels. Path analysis identified plant height, days to 50% flowering, days to harvesting, seeds per plant, pods per plant, and thousand-seed weight as having positive direct effects on yield per plant, implying that selection for these traits could enhance cowpea yield. Among the evaluated genotypes, E25 stood out as the highest yielding with 533.33 g yield per plant, early maturity at 84 days after sowing, moderate thousand-seed weight (124.33 g), seeds per plant (13.87), and plant height (103.33 cm), making it a promising candidate for hybridization. This research provides valuable insights for cowpea breeding programs, highlighting the importance of selecting specific traits like plant height, flowering time, and thousand-seed weight to develop high-yielding, resilient cowpea varieties adaptable to diverse agricultural conditions.Asian J. Med. Biol. Res. 2024, 10(4), 148-156